Wine and Oil - Kykeion and Istrian Supa - Milićević Bradač, Marina (Array, 2007)
Wine is a well known commodity from the prehistoric times and was consumed in many different ways. Equally oil was known for a very long time and was gradually gaining importance in the Mediterranean diet. It is therefore not surprising that the combination of wine and other food - cheese, oil, spices, honey and specially fried corn or bread, was common diet. Famous is the Homeric kykeố n and that particular way of preparing dishes with wine survived until modern times, e.g. in Istria, where the so called Istrian supa is the national specialty.